Conduction mechanisms in P(VDF-TrFE)/gold nanowire composites: tunnelling and thermally-activated hopping process near the percolation threshold. (19th August 2016) - Ramachandran, Laavanya; Lonjon, Antoine; Demont, Philippe; Dantras, Eric; Lacabanne, Colette
Abstract: High-aspect ratio gold nanowires were dispersed in a P(VDF-TrFE) matrix to form conducting polymer composites. The composites were found to follow a percolation law, with a low percolation threshold of 2.2%vol and attaining a conductivity value of 100 S m −1 . The temperature and frequency dependence of the composites were studied using broadband dielectric spectroscopy. Tunnelling was found to be the main charge transport mechanism at temperatures below −100 °C and a thermally-activated hopping mechanism was determined to be responsible for conduction at temperatures above −100 °C. The correlated barrier hopping model was found to be the best fit to explain the conduction mechanisms in the composites.